Implementation of Improved Accounting and Digital Marketing Applications at Binoemar Roastery MSMEs - Diana Dwi Astuti; Nely Supeni (TGO Journal of Community Development, 2023)
The community service activities that we carry out are to help MSMEs survive and develop in the future. Our implementation of community service is providing training, assistance, and motivation to remain sustainable in entrepreneurship for MSMEs. Community service activities were carried out on July-August 2023 at Binoemar Roastery MSMEs, Krajan Hamlet, Banyuwangi. This MSME is engaged in processing coffee beans and opening a coffee cafe. The production results include Original Coffee Powder with Arabica, House Blend, Excelsa, Lanang Coffee, and Robusta types. Apart from selling ground coffee, it also sells mature coffee beans under the name Authentik. Gold sizes start from Small, Large, Jumbo, Premium, and Gold. Apart from that, it also sells golden packages that can be directly brewed, namely K-POP, at a price of Rp. 8,000,-. The original sales system was by leaving it in souvenir shops in Banyuwangi Regency. Binoemar Roastery has not recorded income and expenses from its business. As a result of training and mentoring at Binoemar Roastery with various problems, we provided assistance for 1 month. So the result of what we do is provide a simple form of bookkeeping in Excel form and accompany its operation. Create digital marketing through the Shopee and TikTok applications.